Strategi Pembelajaran Membaca Permulaan pada Peserta Didik Berkebutuhan Khusus - Iir Hafsoh Azzahra; Arin Rahma Silfiya; Ella Safitri; Fenika Pratiwi; Muhamad Mafrukhin; Fenita Akromah; Hamidulloh Ibda; Pradicka Zahra Pertiwi (LPPM STAI Al-Azhar Menganti Gresik, 2023)
Proper education is a citizen's right. This is stated in Article 31 Paragraph 1 of the 1945 Constitution, which states that every citizen has the right to education. One form of implementation is schools for children with special needs, which are provided specifically to educate students with special needs (PDBK). Schools for children with special needs in Indonesia are regular schools, special schools (SLB), and inclusive schools intended to realize and guarantee education for all. This research aims to reveal the efforts made by SD Tumbuh 1 in creating effective strategies for learning beginning reading for children with special needs. The sources of this research are the principal, vice principal, counselling guidance teacher, special needs companion teacher, homeroom teacher and all teachers and staff at SD Tumbuh 1 Yogyakarta. Sampling was conducted in classes 1A and 1B, which comprised 21 students. Observation techniques, in-depth interviews, and document studies were applied to obtain data. Data analysis was carried out using qualitative descriptive analysis, which includes data reduction, data presentation, and conclusion drawing. The results showed efforts to create effective strategies in learning beginning reading for grade 1 at SD Tumbuh 1 Yogyakarta. First, repetition strategies with challenges are effective for learning beginning reading for children with special needs at SD Tumbuh 1 Yogyakarta. Second, the ease of regular students and students with special needs at SD Tumbuh 1 Yogyakarta, in the beginning, reading using repetition strategies in every lesson.